A Case Study of Co-production Within a Mental Health Recovery College Dementia Course: Perspectives of A Person With Dementia, Their Family Supporter and Mental Health Staff - West, Juniper; Birt, Linda; Wilson, Danielle; Mathie, Elspeth; Poland, Fiona (Frontiers in Rehabilitation Sciences, 2022)
Background Undertaking co-production as a power-sharing way to improve mental health dementia services remains uncommon, suggesting opportunities to apply knowledge from lived experience of people with dementia, may often be missed. One barrier to overcome is stigma, assuming people with progressive cognitive impairment cannot manage this level of participation, support peers nor offer a ‘valid’ perspective. Purpose This paper shares knowledge from a service evaluation exploring various experiences of a person with dementia, their family supporter and staff involved in co-producing a dementia course within a mental health Recovery College. Design A qualitative, case study approach used semi-structured interviewing and inductive thematic analysis. Findings Co-production activities generated a shared sense of positivity, pride and privilege, highlighting positive effects of co-production in breaking down ‘them and us’ barriers common in traditional healthcare professional-service user relationships, and ensuring each individual had both something to offer and something to gain in the process. Staff identified challenges; in that balancing all the voices during meetings could be complex at times, and the co-production process overall required considerable time commitment. Conclusion Participating in co-production with peer support is a relational activity which was seen to be valuable in gently, but powerfully, challenging stigma and assumptions around dementia. Findings establish that although the process of co-production requires time and dedication, value can be seen overall in involving people living with dementia both in co-production and in peer support, as a straightforward and beneficial means to inclusively improve post-diagnosis support and care quality within a memory service.